The emerging role of mitochondria in the pharmacological and toxicological effects of Tripterygium wilfordii Hook F: functions, targets and new therapeutic applications - Zhonghao Liu; Dan Li; Xiongwen Yang; Xisha Chen; Chengxiao Fu (Chinese Medicine)
Abstract Tripterygium wilfordii Hook F (TWHF) is a traditional Chinese medicine with multifaceted pharmacological properties, has faced clinical application challenges due to its dose-limiting organ toxicity. Through a systematic analysis of current literature, this review deciphers the dual regulatory role of mitochondrial function in mediating both therapeutic efficacy and adverse effects of TWHF-derived active compounds. We elucidate that processes such as mitochondrial biogenesis, mitochondrial fusion and fission, mitophagy and mitochondrial apoptosis pathways influence the therapeutic efficacy and adverse effects of TWHF active ingredients. In addition, we review innovative dosage forms and derivatives of TWHF that exploit mitochondrial targeting to enhance their pharmacological efficacy. This article offers a concise overview pharmacological and toxicological effects of the principal active components of TWHF, in particular triptolide and celastrol, with a particular emphasis on elucidating the critical role of mitochondria in these processes. Further high-quality basic studies are essential to strengthen the link between mitochondrial function and the active compounds of TWHF, offering more diverse options for their clinical development. Graphical Abstract